Tourism Digital Marketing based on the Sustainability Model in Bali - Sembiring, Susanna Silvia; Thanos, Guellica Agnesia Claudia (Jurnal Komunikasi Profesional, 2025)
Tourism destinations increasingly rely on digital communication strategies to balance economic growth with environmental and cultural preservation. This study examines the implementation of a sustainability-based digital marketing model within Bali’s tourism industry, emphasizing how digital communication supports sustainable destination branding and stakeholder engagement. Using a mixed-method approach, this research integrates content analysis of digital platforms, in-depth interviews with tourism practitioners, and visitor perception surveys to identify key sustainability narratives. Findings indicate that effective digital storytelling centered on local culture, environmental responsibility, and community empowerment significantly enhances tourists’ trust and loyalty while mitigating overtourism pressure. Social media and website analytics demonstrate that campaigns highlighting authentic, eco-conscious experiences produce higher engagement and conversion rates compared to traditional promotional strategies. Moreover, the study underscores the critical role of communicative transparency and co-creation between stakeholders in sustaining Bali’s image as a responsible global tourism hub. This research contributes to communication and marketing scholarship by proposing an integrative framework linking sustainability communication, digital marketing innovation, and destination competitiveness. The model offers practical guidance for policymakers, tourism boards, and marketers seeking to implement ethical, sustainable, and digitally driven promotional strategies in other global destinations.